Bio-based graphene-coated Co@CS catalysts are used to selectively hydrogenate nitriles to prepare primary amines via flow synthesis under mild conditions - Siyi Mi; Jianguo Liu (Results in Chemistry)
Amines are basic components of bioactive compounds, natural products, drugs, and functional materials. Catalytic hydrogenation of nitrile compounds to corresponding amines is a green and efficient production method. Compared with heterogenous metal catalyzed batch reactions in high pressure of hydrogen, the flow synthesis method using heterogeneous metal catalysts can achieve higher catalyst efficiency and productivity, as well as much safer practical application. Moreover, the development of multiple utilizations of sustainable biomass materials especially in developing biobased materials for catalysts is highly demanding. So in this work, advanced flow synthesis methodology was used to prepare primary amines via bio-based chitosan Co@CS heterogeneous catalyst through the catalytic hydrogenation of nitrile. The effects of temperature, pressure, ammonia concentration, and liquid flow rate on the flow reaction were investigated. Under the optimal reaction conditions, the benzonitrile (BN) conversion rate was greater than 99 %, and the selectivity of benzylamine exceeded 99 %. The synthesized graphene-encapsulated Co-based catalyst with chitosan as the carrier material was tested for a long time to verify the stability of the Co@CS catalyst. The substrate expansion experiments of various aromatic nitriles gave satisfactory primary amine yields. Due to its exceptional mass and heat transport properties, the H-Flow system offers an efficient route for the large-scale synthesis of primary amines from biomass platform compounds in industrial production. This study provides new ideas and references for preparing highly selective primary amines by industrial-scale hydrogenation of nitrile compounds.